Money Is the Root of Asset Bubbles - Yu Awaya; Kohei Iwasaki; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper examines how monetary expansion causes asset bubbles. When there is no monetary expansion, a bubbly asset is not created due to a hold-up problem. Monetary expansion increases buyers' money holdings, and then, dealers are willing to buy a worthless asset from sellers, in hopes of selling it to buyers who may not know that it is worthless—a bubble now occurs.
Keywords: D82; D83; D84; E44; E52; G12; G14; 330; bubbles; dealers; higher-order uncertainty; money